2016
DOI: 10.18632/oncotarget.8253
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog pathway maintains cell survival under stress conditions, and drives drug resistance in lung adenocarcinoma

Abstract: Hedgehog (HH) pathway plays an important role in embryonic development, but is largely inactive in adult except for tissue repair. Aberrant activation of HH pathway has been found in a variety of cancer types. In non-small cell lung cancer, however, the role and importance of HH pathway remain controversial. In the current study, we found that HH pathway was maintained in low activity in lung adenocarcinoma (LAC) cells under normal culture condition, but was highly induced in response to stress conditions. Act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 37 publications
3
33
0
Order By: Relevance
“…Infact, protein lysates from harvested resistant tumors showed higher vimentin levels and EGFR-inhibitors resistant cancer cells established in vitro showed high invasive and migrative abilities. Consistently with our previous findings, Hh signaling was confirmed as an important mediator of resistance to EGFR-TKIs inhibitors for first-generation EGFR-TKIs [6, 3032]. Further, in the present study, we demonstrated that Hh activation is involved also in resistance to second and third generation EGFR-TKIs.…”
Section: Discussionsupporting
confidence: 93%
“…Infact, protein lysates from harvested resistant tumors showed higher vimentin levels and EGFR-inhibitors resistant cancer cells established in vitro showed high invasive and migrative abilities. Consistently with our previous findings, Hh signaling was confirmed as an important mediator of resistance to EGFR-TKIs inhibitors for first-generation EGFR-TKIs [6, 3032]. Further, in the present study, we demonstrated that Hh activation is involved also in resistance to second and third generation EGFR-TKIs.…”
Section: Discussionsupporting
confidence: 93%
“…The Hedgehog pathway has been found to regulate autophagy and EMT [2426]. Thus, we first evaluated by quantitative real time PCR (qRT-PCR) the expression of different members of Hedgehog signaling pathway, Shh, Ihh and Dhh ligands, their specific receptors, Patched 1 and 2 (Ptch1 and Ptch2) and some related genes such as Zeb1, Zeb2, ALCAM and VEGFA in BC cells treated with CPS for 120 h. Upregulation of the Dhh/Ptch2/Zeb2 pathway as well as downregulation of Shh or Ihh/Ptch1/Zeb1 genes were observed in CPS-treated BC cells as respect to untreated cells.…”
Section: Resultsmentioning
confidence: 99%
“…Hedgehog signaling pathway activation is positively correlated with chemoresitance in cancer cells [24, 27]. Thus, we finally investigated the drug-sensitivity of CPS-induced EMT cells to chemotherapeutic agents commonly used in BC therapy.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, Hh signaling can regulate cancer stem cell numbers as well as the tumor microenvironment, creating conditions that promote tumor growth. This role of Hh signaling can be found in leukemia and liver cancer, and is often responsible for the recurrence of cancer through resistance to chemotherapy and radiotherapy 2433. Dys-regulation of any component of the Hh pathway leading to its aberrant activation can result in malignant conditions through these mechanisms.…”
Section: The Hh Pathway In Cancer Developmentmentioning
confidence: 99%